On the Implementation of Interdisciplinary Relationships in Classes in Chemistry with Disciplines of the Professional Cycle (Eurasian Journal of Learning and Academic Teaching, 2023)
This article describes the methodology and tasks of developing the structure of practical and experimental classes in chemistry based on interdisciplinarity